Effect of three substrates and two formulas of fertilizers in seedling growth cocoa (Theobroma cacao L.), Naranjal, Guayas province - Vargas Guillén, Pablo Israel; Tenesaca Sumba, Walter Armando; Centanaro Quiróz, Paulo Humberto; Peña Haro, César Antonio (SATHIRI, 2024)
Cocoa is one of the crops with the greatest presence in the national and international market, contributing significantly to the country’s GDP, this importance triggers the analysis and promotion of tools, strategies, and processes that make its production even more viable, thus proposing different promising alternatives, such as the need to obtain cocoa cultivars, using various types of substrates (chicken manure 50 + humus 50%, sawdust 50% + humus 50%, loamy soil) and two NPK formulas to evaluate plant growth and development cocoa in nursery. For the development of the trial, the distribution of the Completely Random Design (DCA) was used, with AxB factorial arrangement, with 6 treatments; each one of them was evaluated by means of 4 repetitions. The effect of the substrates on the study variables was evaluated: stem diameter (mm), root length (cm), number of leaves per plant, plant height (cm), plant vigor (%). The addition of NPK to the loam soil significantly improved the growth and development of cocoa plants in nurseries, thus having T6 Loam soil (NPK 8-24-8), as the treatment that presents the best results in each of the variables evaluated. , having as evidence the averages of the vigor of the plant with 92.5%. This factor also leaves a net benefit of 197, and a benefit/cost ratio of 1.57.